MENJAGA EKSPRESI BUDAYA TRADISIONAL DI INDONESIA - Ayu Citra Setyaningtyas; Endang Sri Kawuryan (Sekolah Tinggi Ilmu Hukum Tambun Bungai Palangka Raya, 2016)
Indonesia is a country with remarkable potentialities of traditional culture expressions and traditional culture legacies. Both traditional culture expressions and traditional culture legacies take place in several forms such as folktales, dances, graving arts, weaving arts, and other still-unrevealed traditional culture expressions which may be useful for economic development in Indonesia. All traditional culture expressions and traditional culture legacies are the product of human thoughts that can be transferred and captured by human senses. However, many of Indonesian traditional culture expressions and traditional culture legacies have been claimed by other countries, especially developed countries, without asking permission from Indonesia. Nowadays, developing countries, including Indonesia, must encounter the injustice issue related to the utilization of their traditional culture expressions and traditional culture legacies. However, regulatory system is not strong enough to provide the protection needed for traditional culture expressions and traditional culture legacies. The utilization of traditional culture expressions and traditional culture legacies can be then defined as the use of traditional culture expressions as commercial assets without giving chance for developed countries to take benefits from Indonesia. Therefore, a special arrangement must be made to protect traditional culture expressions and traditional culture legacies.